(untitled) (Studia theodisca, 2016)
Both as essay writer and poet Ludwig Rubiner (1881-1920) focuses on art as a revolutionary practice. He conceives critical understanding of reality as a first step in a radical change of social conditions, which can be seen as the result of an artist’s specific attitude in evoking new worlds. This implies that only a non-realistic art can be politically successful, because it refers to a future horizon without restricting itself to describing the political situation of the time. In this paper, I analyze Rubiner’s strongly utopic art concept involving some typical categories of expressionistic literature like “Geist”, “Gemeinschaft”, “Katastrophe”.